Dietary calcium to phosphorus ratio affects postprandial phosphorus concentrations in feline plasma. Issue 9 (14th November 2022) - Coltherd, Jennifer Carolyn; Staunton, Ruth; Colyer, Alison; Gilham, Matthew; Rawlings, John; Alexander, Janet E.; Logan, Darren W.; Butterwick, Richard; Watson, Phillip; Bakke, Anne Marie
Abstract: The impact of dietary phosphorus on chronic renal disease in cats, humans and other species is receiving increasing attention. As Ca and P metabolism are linked, the ratio of Ca:P is an important factor for consideration when formulating diets for cats and other animals. Here, we describe a fully randomised crossover study including twenty-four healthy, neutered adult cats, investigating postprandial responses in plasma P, ionised Ca and parathyroid hormone (PTH) following one meal (50 % of individual metabolic energy requirement) of each of six experimental diets. Diets were formulated to provide P at either 0·75 or 1·5 g/1000 kcal (4184 kJ) from the soluble phosphorus salt sodium tripolyphosphate (STPP, Na5 P3 O10 ), variable levels of organic Ca and P sources, and an intended total Ca:P of about 1·0, 1·5 or 2·0. For each experimental diet, baseline fasted blood samples were collected prior to the meal, and serial blood samples collected hourly for 6 h thereafter. For all diets, a significant increase from baseline was observed at 120 min in plasma PTH ( P < 0·001). The diet containing the highest STPP inclusion level and lowest Ca:P induced the highest peaks in postprandial plasma P and PTH levels (1·8 mmol/l and 27·2 pg/ml, respectively), and the longest duration of concentrations raised above baseline were observed at 3 h for P and 6 h for PTH. Data indicate that Ca:P modulates postprandial plasma P and PTH. Therefore, when formulating diets containing soluble P salts for cats, increasing the Ca:P ratio should be considered.